2014
DOI: 10.1088/0964-1726/23/9/095016
|View full text |Cite
|
Sign up to set email alerts
|

Phase field simulations of the poling process and nonlinear behavior of ferroelectric polycrystals with semiconducting grain boundaries

Abstract: The effect of grain boundary conductivity on the poling process and the nonlinear electromechanical behaviors of ferroelectric polycrystals are investigated through the use of a phase field model. The grain boundary is modeled as a semiconductor in the phase field model via Maxwell’s equations, which consider the drift of free charges under an electric field. The simulation results show that the poling electric field of the ferroelectric polycrystal with the semiconducting grain boundary is much larger than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A phasefield model of polycrystal ferroelectrics was first proposed by Choudhury et al (99), and similar models were later applied to study the effects of grain orientation (104), grain boundary width (64), and grain boundary semiconduction (105) on switching behaviors. Generally, the P-E loop shrinks with a decrease in grain size and with an increase in grain misorientation (61) and can be largely tilted and diminished if the grain boundary becomes conductive (105). Recently, Su and coworkers (63,100,106) further examined this topic by systematically investigating the grain size effect with finer grains down to 10 nm under cyclic fields with a frequency of up to 2,500 Hz.…”
Section: Simulation Of Ferroelectric Hysteresis Loopsmentioning
confidence: 99%
“…A phasefield model of polycrystal ferroelectrics was first proposed by Choudhury et al (99), and similar models were later applied to study the effects of grain orientation (104), grain boundary width (64), and grain boundary semiconduction (105) on switching behaviors. Generally, the P-E loop shrinks with a decrease in grain size and with an increase in grain misorientation (61) and can be largely tilted and diminished if the grain boundary becomes conductive (105). Recently, Su and coworkers (63,100,106) further examined this topic by systematically investigating the grain size effect with finer grains down to 10 nm under cyclic fields with a frequency of up to 2,500 Hz.…”
Section: Simulation Of Ferroelectric Hysteresis Loopsmentioning
confidence: 99%
“…In what follows, we refer to the free energy density for lead-titanate (PbTiO 3 ), which is a ferroelectric material with cubic symmetry, widely discussed in the literature (see, e.g. [54][55][56][57]59] and [34,51,61,64]).…”
Section: Mech Elecmentioning
confidence: 99%
“…Actually, the structure of ferroelectric thin films in FeFETs is generally polycrystalline film which is composed of grain boundary and grain orientation. The grain boundary and grain orientation have a significant effect on the C–V relation curve and the output characteristic curve of FeFETs through the remnant polarization value and the coercive field of ferroelectric films . It has been reported that hysteresis loops with different grain orientations are distinguishing, particularly in their coercive fields .…”
Section: Introductionmentioning
confidence: 99%